Coaching the 400-m-hurdles - Bell, S.
I Introduction II Evolution of the Hurdle III History of the 400-meter Hurdles IV Records V Attributes of a Champion VI Hurdling Terms Defined VII Warm up and Stretching VIII Approach to the First Hurdle IX Approach to the Second Hurdle X Sprinting Between the Hurdles XI Coaching Tips XII Training Schedules XIII Complete Text XIV Sam Bell Resume'